THE ROLE OF COGNITION AND THE ONSET OF MAJOR MOBILITY DISABILITY IN OLDER ADULTS: RESULTS FROM THE LIFE STUDY. (11th November 2018) - Handing, E; Kritchevsky, S; Chen, H; Rosso, A; Manini, T; Rejeski, J
Abstract: Mobility and cognition are critical aspects for an older adult to remain independent, and self-reported mobility as measured by the Mobility Assessment Tool-short form (MAT-sf) can predict future onset of mobility disability. This study examines if baseline cognitive function and the MAT-sf serve as independent or synergistic factors in the development of major mobility disability (MMD). Data was collected from 1, 635 adults 70–89 years old, free of MMD at baseline from the LIFE study. Cognitive function was categorized into four domains; global cognition, processing speed, verbal memory, and executive function. Self-reported mobility was measured using the MAT-sf, an innovative video animation tool assessing a variety of mobility tasks which asks participants to rate their ability to perform each task. MMD was defined as the inability to walk 400m in < 15 minutes at one or more time points during the study (average of 2.6 years). Of the 1635 participants at baseline, 536 (32.8%) developed MMD. Better baseline cognitive function was significantly related to faster 400m gait speed and a higher score on the SPPB at baseline (β range 0.076–0.172, p's <0.01); however, cognition was not related to MAT-sf scores. Cox Proportional Hazard models indicate an independent relationship between processing speed (HR: 0.84, 95% CI 0.75–0.93, p= 0.002), executive function (HR: 0.85, 95% CI 0.77–0.93, p=0.001) and the MAT-sf (HR: 0.64, 95% CI:0.58–0.72, p <.001) on incidence of MMD. The MAT-sf serves as a strong risk factor in predicting MMD in older adults independent of cognitive functioning.